Effects of multi-sequence combination forces on creep characteristics of bales during wheat harvesting - Tang, Zhong; Liang, Yaquan; Zhang, Ben; Wang, Meiling; Zhang, Hao; Li, Yaoming (International Journal of Agricultural and Biological Engineering, 2021)
During the baling operation, the wheat stalks are subjected to various mechanisms in the baler and the main form is compression. After the wheat stem is forced by a combination of the threshing cylinder, it needs to be formed under the action of straw baler and meet transport requirements. This paper mainly studies the properties of wheat stalks when baling, and proposes the application of the creep after-effect theory during the baling process. The tension-compression tester is used to perform 50 mm stalk mechanical test, 50 mm stalk static pressure test, 35 mm×40 mm× 50 mm stalk module static pressure test and bale static pressure test. The measured elastic modulus of the stem sample is 7.59 MPa, and the elastic modulus of the inner core of the stem is 8.24 MPa. The return curve of the single stalk and the bale is consistent with the initial creep and steady-state creep in the creep after-effect theory. A logarithmic function was used for fitting of the first stage with coefficient of determination R2 = 0.8364, and a linear function was used for fitting of the second stage with coefficient of determination R2 = 0.9921. The high water content static pressure test suggests that the load in the loading direction is the coupled load of the working load of the hydraulic cylinder and the internal stress of the bale. When harvesting wheat stalks with high moisture content, the density parameter of the bale can be appropriately increased while the load parameter of the hydraulic cylinder can be considered unchanged or even reduced. The adjustment of density and load can still ensure the forming quality of the bale.Keywords: baler, rheological properties, wheat stalk, mechanical propertiesDOI: 10.25165/j.ijabe.20211405.6265Citation: Tang Z, Liang Y Q, Zhang B, Wang M L, Zhang H, Li Y M. Effects of multi-sequence combination forces on creep characteristics of bales during wheat harvesting. Int J Agric & Biol Eng, 2021; 14(5): 88–99.